👤

Calculati: 4^14-(6*4^13-2*2^26)

Răspuns :

[tex] {4}^{14} - (6 \times {4}^{13} - 2 \times {2}^{26} )[/tex]

[tex] ={( {2}^{2} )}^{14} - [6 \times {( {2}^{2} )}^{13} - 2 \times {2}^{26} ][/tex]

[tex] = {2}^{2 \times 14} - (6 \times {2}^{2 \times 13} - 2 \times {2}^{26} )[/tex]

[tex] = {2}^{28} - (6 \times {2}^{26} - 2 \times {2}^{26} )[/tex]

[tex] = {2}^{28} - [ {2}^{26}(6 - 2) ][/tex]

[tex] = {2}^{28} - {2}^{26} \times 4[/tex]

[tex] = {2}^{28} - {2}^{26} \times {2}^{2} [/tex]

[tex] = {2}^{28} - {2}^{26 + 2} [/tex]

[tex] = {2}^{28} - {2}^{28} [/tex]

[tex] = 0[/tex]